2018
DOI: 10.3390/toxins10070289
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a New Zealand White Rabbit Model for Lethal Toxin (LT) Challenge and Efficacy of Monoclonal Antibody 5E11 in the LT-Challenged Rabbit Model

Abstract: Anthrax caused by Bacillus anthracis is a lethal infectious disease, especially when inhaled, and the mortality rate approaches 100% without treatment. The anthrax antitoxin monoclonal antibody (MAb) 5E11 is a humanized antibody that targets the anthrax protective antigen (PA). The efficacy of 5E11 needs proper animal models. However, anthrax spores are extremely dangerous, so experiments must be conducted under Biosafety Level 3 conditions. Considering the critical effects of lethal toxin (LT) on hosts during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The mice in the control group were administrated the isotype mAb 5E11. 46 The mouse weights and survival were recorded daily for 14 days post-infection. In addition, mouse lung tissues were collected at 3 days post-infection for the assessment of virus replication and histopathological changes.…”
Section: Methodsmentioning
confidence: 99%
“…The mice in the control group were administrated the isotype mAb 5E11. 46 The mouse weights and survival were recorded daily for 14 days post-infection. In addition, mouse lung tissues were collected at 3 days post-infection for the assessment of virus replication and histopathological changes.…”
Section: Methodsmentioning
confidence: 99%
“…Increased permeability with LT exposure at either the alveolar endothelial or epithelial levels or both could produce direct alveolar protein and fluid accumulation, ventilation and perfusion mismatching, and hypoxia and reduced lung compliance. Histopathology studies have demonstrated alveolar protein and fluid accumulation in some but not all models (13,28,39,64). Permeability increases in the pleural visceral or parietal tissues, could also contribute to the recurrent pleural effusions that characterize inhalational anthrax disease.…”
Section: Pulmonary µG µG µGmentioning
confidence: 99%